دور الخبرة القضائية في حل المنازعات العقارية - أحمد, عيادي (جامعة الوادي University of Eloued, 2019)
" ملخص الدراسة : تتناول هذه الدراسة دور الخبرة القضائية في مجال المنازعات العقارية و حلها، فقد قمت بداية بدراسة الجانب النظري في الخبرة القضائية من خلال الفصل الأول ، و الذي جاء بعنوان ماهية الخبرة القضائية ، الذي يحتوي مبحثين ، فالمبحث الأول درست فيه مفهوم الخبرة القضائية ، أما المبحث الثاني فقد تناولت النظام القانوني لها في الميدان العقاري، ثم انتقلت للفصل الثاني الذي قمت فيه بدراسة دور الخبرة القضائية من خلال مبحثين ، الأول بعنوان تقرير الخبرة القضائية و ما يحتويه من إجراءات شكلية، أما المبحث الثاني فجاء فيه بعض الصور من الخبرة القضائية للمحكمة العليا. " "Study summary This study deals with the role of judicial expertise in the filed of real estate disputes, I have started by studying the theoretical aspect of judicial experience through the first chapter wich is entitled what is judicial experience which contains two subjects the first study examined the concept of judicial experience in the fieled of real estate and then moved to the second chapter in wich I studied the role of judicial expertise throught the first two sections entitled report of the experience of the judiciary and the contents of the formal procedures the second section in wich he hade someb photographs of judicial experience in the suqreme court. "
ماستر اداري
Keywords: الخبرة، المنازعات، القاضي ،الاثبات ، الخبير، المحكمة،العقار .; experience,disputes, the judge,proof, the expert, court, real estat.